2005
DOI: 10.1074/jbc.m413159200
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional Disfavor for Proline at the P+1 Position among AGC and CAMK Kinases Establishes Reciprocal Specificity between Them and the Proline-directed Kinases

Abstract: To precisely regulate critical signaling pathways, two kinases that phosphorylate distinct sites on the same protein substrate must have mutually exclusive specificity. Evolution could assure this by designing families of kinase such as basophilic kinases and proline-directed kinase with distinct peptide specificity; their reciprocal peptide specificity would have to be very complete, since recruitment of substrate allows phosphorylation of even rather poor phosphorylation sites in a protein. Here we report a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 35 publications
1
66
0
Order By: Relevance
“…Because S 0 P ϩ1 and T 0 P ϩ1 motifs are likely targets of Cdks or MAP kinases, 35 but not of the other kinases, 53 these results suggested Cdk/cyclin-dependent phosphorylation of Flag⌬NTGATA2 at S 0 P ϩ1 or T 0 P ϩ1 motifs.…”
Section: Phosphorylation and Interaction With Cdk/cyclinmentioning
confidence: 77%
“…Because S 0 P ϩ1 and T 0 P ϩ1 motifs are likely targets of Cdks or MAP kinases, 35 but not of the other kinases, 53 these results suggested Cdk/cyclin-dependent phosphorylation of Flag⌬NTGATA2 at S 0 P ϩ1 or T 0 P ϩ1 motifs.…”
Section: Phosphorylation and Interaction With Cdk/cyclinmentioning
confidence: 77%
“…Another inhibitory phosphorylation site on eNOS that may be phosphorylated by a PKC isoform is Ser116. Kou et al (2002) showed that the PKC inhibitor calphostin could reduce eNOS Ser116 phosphorylation; however, others have shown that PKC cannot phosphorylate eNOS Ser116 because it is followed by a proline (Fujii et al, 2004;Zhu et al, 2005). Therefore, although FK506 may be having an indirect effect on Ser116, it is not related directly to the PKC-mediated phosphorylation of eNOS Thr495 induced by FK506 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This conformation appears to be stabilized in part by an interaction between the backbone carbonyl of the residue immediately upstream (Asp-202) and the side chain of Ser-189 at the start of the activation loop. As noted by Shaw and co-workers (54,55) for other kinases belonging to the AGC and CAMK groups, Pim kinases appear to strongly deselect Pro in the ϩ1 position in substrates. This "proline disfavor" phenomenon is generally attributable to the inability of Pro to hydrogen bond to the carbonyl group of the residue equivalent to Gly-203 in the kinase.…”
Section: Structures Of Pim-1 In Complex With a Consensus Peptide And mentioning
confidence: 92%